Age and Attitude are Dominant Factors Related to Health Workers' Preparedness in Dealing with Flood Disasters - Astuti, Novi Dwi; Admasari, Yuli; Sarliana, Sarliana (EMBRIO: Jurnal Kebidanan, 2025)
Indonesia has a relatively high threat of disasters, including floods that result in human casualties, environmental damage, property losses, and psychological impacts. Prevention efforts need to be carried out, namely mitigation and preparedness. Central Sulawesi Province is the 9th out of 10 provinces in Indonesia that are often affected by disasters. Sigi Regency is a flood-prone area. In 2021, there have been eight floods in Rogo and Wisolo villages. Health workers are important and technical implementers before, during, and after disasters. The purpose of this study is to look at the factors that affect the preparedness of health workers in dealing with flood disasters at the Baluase Health Center. Analytical survey research with a cross-sectional approach. The sample is all health workers at the Baluase Health Center, totaling 44 people. The independent variables are age, gender, length of work, level of education, knowledge, and attitude. In contrast, the dependent variable is the preparedness of health workers in dealing with flood disaster situations. Questionnaires are used in primary data collection. The multivariate analysis of logistic regression variables in step 5 found a relationship between age (p equals 0.028), attitude (p equals 0.052), and preparedness of health workers in dealing with flood disasters. It is hoped that the increase in preparedness for health workers will continue to be improved to reduce the post-disaster impact.